Development of a Digital-Spiritual Leadership Model for School Principals to Improve Work Engagement and Teacher Performance in the Era of Educational Transformation - Rita Prima Bendriyanti; Suwarni (Attractive : Innovative Education Journal, 2026)
The educational transformation marked by the integration of digital technology into the learning process and school governance requires principals to develop leadership models that are adaptive to the dynamics of the times without abandoning their foundation in spiritual values. Challenges in the technological era are not solely related to technical skills in operating digital devices, but also to the capacity to build a meaningful work culture, uphold integrity, and be oriented towards the quality of educational services. This research aims to develop and validate the Digital–Spiritual Leadership model for principals as a strategy to improve work engagement and teacher performance. The method applied is Research and Development (R&D) with stages of needs analysis, conceptual design, expert validation, limited trials, and comprehensive testing of the model's effectiveness. Data were obtained through questionnaires, in-depth interviews, and document reviews. Then, they were analyzed descriptively quantitatively with the help of tables and graphs to map changes in teacher engagement and performance indicators. The results show a significant increase in the dimensions of work enthusiasm, professional commitment, and active involvement in carrying out tasks after the model's implementation. In addition, the quality of lesson planning, innovation in pedagogical practices, and achievement of performance targets showed an increasing trend. The analysis of the discussion confirms that integrating digital competencies with strengthening spiritual values creates inspiring leadership that has a broad impact on the school system. Therefore, the resulting Digital–Spiritual Leadership model is deemed relevant and effective in strengthening work engagement and improving teacher performance in the context of educational transformation.